Live-cell imaging reveals decreased cAMP in a PFE-associated c.1050-3C>G PTH1R cell model - K. Marnet; H. Subramanian; M. Wiesler; A. Borst; D. Liedtke; G. Pattappa; D. Docheva; V. O. Nikolaev; A. Stellzig-Eisenhauer; M. Eigenthaler; M. Herrmann (Journal of Molecular Medicine, 2026)
Primary failure of eruption (PFE) is a rare autosomal disorder provoked by heterozygous mutations in the parathyroid hormone receptor 1 ( PTH1R ) gene. PTH1R is a G protein-coupled receptor (GPCR) which regulates intracellular signaling molecules like cAMP. By using CRISPR/Cas9, the pathogenic PTH1R variant, c.1050-3C>G, was introduced into the periodontal ligament (PDL-hTERT) cell line to investigate molecular mechanisms in a PFE in vitro model. The PDL-hTERT immortal cell line, derived from human primary PDL cells, is a well-established model for dental diseases and expresses PTH1R . We performed different functional assays to compare the behavior of the PDL-hTERT WT versus PTH1R -mutated cells. cAMP synthesis and PKA activation were compared between different cell lines by live-cell imaging using Förster Resonance Energy Transfer (FRET)-based biosensors. Phosphorylation of VASP was measured to validate and compare the PKA activation between the cell lines. In summary, our experiments show that the mutated cell line has no major phenotypic changes, but the PTH1R downstream signaling cascade is impaired. Key messages A rare autosomal disorder linked to mutations in the PTH1R gene, which encodes a G protein-coupled receptor regulating intracellular signaling, including cAMP production. The pathogenic PTH1R mutation (c.1050-3C>G) was introduced into a periodontal ligament (PDL hTERT) cell line to model PFE and study molecular mechanisms in vitro. Functional assay revealed that while the mutated cell line displayed no major phenotypic changes, the PTH1R downstream signaling cascade, including cAMP synthesis and PKA activation, was disrupted. Techniques like FRET-based biosensors and VASP phosphorylation assays highlighted specific impairments in signaling pathways in cells with the PTH1R mutations

Present-Day Sea Level Variations in Coastal Areas from Daily to Multidecadal Time Scales: Observations and Causes - A. Cazenave; R. Almar; P. Almeida; N. K. Ayoub; J. H. Bettencourt; F. Birol; W. Han; M. Herrmann; S. Jevrejeva; L. Leclercq; F. Niño; J. Oelsmann; et al. (Surveys in Geophysics, 2026)

The carbon dioxide radical anion as a reductant in water treatment and atmospheric chemistry: a review - Thomas Schaefer; Jonathan D. Raff; Mallikarjuna N. Nadagouda; Eric Lichtfouse; Dan Meyerstein; Hartmut Herrmann; Virender K. Sharma (Environmental Chemistry Letters, 2026)
The carbon dioxide radical anion, CO 2 ●− , is a highly reactive radical species involved in the reduction of the CO 2 greenhouse gas, organic synthesis, atmospheric aerosol chemistry, and treatment of halogenated compounds. In recent years, CO 2 ●− has emerged as a strong reductant, or single electron donor. Here we present techniques used to generate CO 2 ●− and we discuss applications to degrading pollutants such as halogenated alkanes. The potential occurrence of such reductions in water and aqueous aerosols is discussed, notably for the degradation of perfluoroalkyl substances. In the laboratory, CO 2 ●− is directly generated by either direct electrochemical reduction of CO 2 or hydrogen atom transfer of either formate salts with and without catalysts or ferrioxalate through photochemical or radiolytic processes. The CO 2 ●− has an ultraviolet spectrum, and CO 2 ●− vibration modes are characterized by fast kinetics using infrared and Raman spectroscopy. The second-order rate constants of the reactions of CO 2 ●− with halogenated alkanes, of -1.84 ± 0.22 V, are generally slower than that of the hydrated electron, of -2.87 V, and give a negative linear relationship with energy of lower unoccupied molecular orbital, suggesting single electron transfer mechanism in reducing the halogenated compounds.

Factors affecting 87Sr/86Sr preservation in conodont apatite: An example from the Ordovician of Baltoscandia - Christopher T. Conwell; Matthew R. Saltzman; Anders Lindskog; Mats E. Eriksson; Elizabeth M. Griffith; Stephen A. Leslie; Cole T. Edwards; Olle Hints; Achim D. Herrmann (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The selenium isotope composition of shallow-marine carbonates from the Bahamas: Implications for seawater paleoredox studies - Benjamin Eickmann; Achim D. Herrmann; Stephan König (Chemical Geology, 2026)

Erratum to “Experimental degassing of moderately volatile chalcophile elements from silicate melt with and without sulfur present” [Geochim. Cosmochim. Acta 402 (2025) 153–172] - William F. Heck; Achim D. Herrmann; Colin R.M. Jackson (Geochimica et Cosmochimica Acta, 2026)

Rebuttal to the response by Millar and Broadhurst - Bent Herrmann; Juan Santos; Manu Sistiaga; Jure Brčić; Junita D. Karlsen; Valentina Melli; Antonello Sala; Tiago Veiga-Malta; Jesse Brinkhof; Andrea Petetta; Mengjie Yu; Mark J.M. Lomeli; et al. (Fisheries Research, 2026)

A fundamental trade‐off among resilience, resistance, efficiency, and redundancy in tidal wetlands - Joshua E. Lerner; Rusty A. Feagin; Thomas P. Huff; Raymond G. Najjar; Astrid Layton; Maria Herrmann; Jose D. Fuentes (Ecology, 2026)
In an era of change, the survival and adaptability of ecosystems will be tested. An optimal ecosystem would be both resistant and resilient to negative disturbance but also efficient and redundant in its growth when given positive subsidies. However, initial evidence has suggested that these properties cannot all be maximized at the same time, and so we sought to quantitatively assess whether there are fundamental trade‐offs between them at the ecosystem level. To achieve this aim, we used a 250‐m resolution NASA MODIS dataset of gross primary productivity (GPP) to monitor 145,871 tidal wetland locations across the conterminous United States every 16 days from March 2000 to December 2020. We quantified the size and duration of the perturbation events in tidal wetland GPP ( n = 13,754,386) and modeled their frequency distributions. Event sizes and recurrence intervals were exponentially distributed and event durations were closely modeled by an inverse power law. This scale‐free manner through which tidal wetlands dissipated perturbations to their GPP flux provided them with long‐term stability across a wide range of geography. We also found that a tidal wetland's positive event responses traded off between properties of efficiency and redundancy, its negative events traded off between resistance and resilience, and that all four properties were orthogonally related to one another. We then constructed a conceptual model to help understand the potential mechanism behind this four‐quadrant trade‐off. The trade‐off appeared to be driven by a feedback between the waiting time and magnitude of positive and negative events, the duration of their effects, and the environmental and physical constraints limiting an ecosystem's growth and productivity. In summary, we detail an emergent pattern of trade‐offs and constraints associated with how tidal wetland ecosystems respond to both positive and negative perturbations in carbon flux.

Letter to the Editor re: Millar and Broadhurst (2025): “Incorrect inference from size-selectivity studies due to widespread misuse of bootstrap confidence bands” [Fisheries Research 281, 107225] - Bent Herrmann; Juan Santos; Manu Sistiaga; Jure Brčić; Junita D. Karlsen; Valentina Melli; Antonello Sala; Tiago Veiga-Malta; Jesse Brinkhof; Andrea Petetta; Mengjie Yu; Mark J.M. Lomeli; et al. (Fisheries Research, 2025)

Artificial intelligence-assisted Ki67 cell counting to aid canine cutaneous mast cell tumour prognostication - D. Walker; A. Herrmann; K. Erles; S. Haugland (Journal of Comparative Pathology, 2025)

Experimental degassing of moderately volatile chalcophile elements from silicate melt with and without sulfur present - William F. Heck; Achim D. Herrmann; Colin R.M. Jackson (Geochimica et Cosmochimica Acta, 2025)

Rapid subsidence as a driver of phosphate deposition in the later Ordovician: Case study from the Alabama Appalachians - John T. Haynes; Rafael A. Villanueva; Richard M. Robinet; Stephen A. Leslie; Achim D. Herrmann (Sedimentary Geology, 2025)

Using species-specific behavior to improve catch efficiency of target species in mixed trawl fisheries - Ludvig A. Krag; Rikke P. Frandsen; Bent Herrmann; Grete E. Dinesen; Junita D. Karlsen (Fisheries Research, 2025)

Can pots be an alternative fishing gear to gillnets? A Mediterranean case study - M. Virgili; A. Petetta; B. Herrmann; K. Cerbule; S. Guicciardi; G. La Manna; L. Malvarosa; D. Li Veli; G. Barone; A. Lucchetti (Reviews in Fish Biology and Fisheries, 2024)
Small-scale coastal fisheries in the Mediterranean often employ gillnets, a widely used gear worldwide. The disadvantages of gillnets in this fishery include high bycatch levels of unwanted species and consequent discards. Moreover, spatial conflict with other gears and dolphin depredation often results in considerable economic loss. Alternative fishing methods are being tested. This study investigated whether, in small-scale fisheries in the Adriatic Sea, pots can ensure sustainable harvest of mantis shrimp ( Squilla mantis ), a major target demersal species in terms of landings, and possibly replace traditional gillnets. We adopted a multidisciplinary approach to investigate the catch efficiency, biological impact, and socio-economic effects of the two fishing methods. We found different species compositions in gillnet and pot catches. Gillnets yielded a greater number of discarded species of no commercial value, whereas pots caught a greater amount of mantis shrimp. Finally, a profit analysis indicated that pot fishery has the potential to increase profits for the commercial fishing industry. This study suggests that pots provide a more sustainable fishing method, both in terms of revenue and environmental impact.

Observing fish behavior in towed fishing gear—is there an influence of artificial light? - Jesse Brinkhof; Manu Sistiaga; Bent Herrmann; Junita D. Karlsen; Eduardo Grimaldo; Nadine Jacques; Zita Bak-Jensen (Reviews in Fish Biology and Fisheries, 2024)
Fish behavior is important to consider when developing selective fishing gear. In studies designed to investigate the size selective properties of towed fishing gears such as trawls, fish behavior is mainly documented by underwater video recordings. Because fishing gear can be operated at great depths or in other low light environments, artificial light is often required for underwater recordings. However, artificial light can influence fish behavior, which casts doubt on the validity of behavioral observations obtained in the presence of artificial light. However, removing artificial light disables video recordings and the possibility to study fish behavior in relation to selectivity devices towed fishing gears in low light environments. To date, little is known about the extent to which artificial light used for video observations affects fish behavior with respect to fishing gear. Therefore, we conducted fishing trials in the Barents Sea demersal trawl fishery to assess the effect of light sources on fish behavior by using size selectivity results in towed fishing gears. We found that the behavior of cod ( Gadus morhua ) was unaffected by the light sources, whereas the behavior of haddock ( Melanogrammus aeglefinus ), saithe ( Pollachius virens ) and redfish ( Sebastes spp.) significantly changed when red light and white light were employed. Our results also demonstrated significant differences in fish behavior between white and red light.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A new certified reference material IAEA-465 for radionuclides in Baltic Sea sediment - M.K. Pham; M.-O. Aust; J. Bartocci; O. Blinova; F.P. Carvalho; E. Chamizo; M. Cook; D. Degering; M. Fujak; C. Gascó; R. Gurriaran; V. Jobbágy; et al. (Journal of Environmental Radioactivity, 2024)

Integrating animals, pasture, and crops within AusFarm for modelling mixed farming - Neville I. Herrmann; Andrew D. Moore; Eric Zurcher (Environmental Modelling & Software, 2024)

Longitudinal relationships between depressive symptoms, functional impairment, and physical activity in later late life - Lisa Y. Xiong; Madeline Wood Alexander; Hugo Cogo-Moreira; Che-Yuan Wu; Michael Eid; Nathan Herrmann; Damien Gallagher; Jodi D. Edwards; Krista L. Lanctôt; Susan Marzolini; David A. Bennett; Jennifer S. Rabin; et al. (GeroScience, 2024)

Cefepime versus carbapenems for treatment of AmpC beta-lactamase-producing Enterobacterales bloodstream infections - Julia Herrmann; Anne-Valérie Burgener-Gasser; Daniel Goldenberger; Jan Roth; Maja Weisser; Pranita D. Tamma; Sarah Tschudin-Sutter (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose Cefepime is recommended for treating infections caused by AmpC beta-lactamase-producing Enterobacterales (AmpC-PE), though supporting evidence is limited. Therefore, this study compared outcomes associated with cefepime versus carbapenem therapy for bloodstream infections (BSIs) caused by AmpC-PE after phenotypic exclusion of ESBL-co-producing isolates. Methods This retrospective cohort study compared definite cefepime versus carbapenem treatment for AmpC-PE BSI in hospitalized patients of the University Hospital Basel, Switzerland, between 01/2015 and 07/2020. Primary outcomes included in-hospital death, renal impairment and neurologic adverse events; secondary outcomes included length of hospital stay and recurrent infection. Results Two hundred and seventy episodes of AmpC-PE BSI were included, 162, 77 and 31 were treated with a carbapenem, cefepime and other antibiotics, respectively. Patients treated with carbapenems were more likely to be transferred to the ICU on admission and more frequently had central venous catheter as a source of infection. In uni- and multivariable analyses, primary and secondary outcomes did not differ between the two treatment groups, except for more frequent occurrence of neurological adverse events among patients treated with carbapenems and shorter length of hospital stay among survivors treated with cefepime. Conclusion After excluding isolates with phenotypic ESBL-co-production, cefepime was not associated with adverse outcomes compared to carbapenems when used to treat BSIs caused by AmpC-PE. Our study provides evidence to support the use of cefepime as a safe treatment strategy for AmpC-PE BSI, particularly in clinically stable patients without initial renal impairment or increased susceptibility to neurological adverse events.

Isolating the drivers of the species‐area relationship in experimental habitat islands - Granger W. Hanks; Natalie A. Clay; Maggie Herrmann; Clifton Nunnally; S. River D. Bryant; Craig R. McClain (Journal of Biogeography, 2024)
Aim Considered one of ecology's laws, the species‐area relationship (SAR) is among the most intensively studied ecological phenomena, yet the mechanisms through which the SAR arises and under what circumstances remain poorly understood. Here, we experimentally test the effects of area alone in the absence of commonly invoked mechanistic drivers of the SAR in both sub‐tidal bay and inter‐tidal marsh habitats. Location Louisiana, U.S.A. Taxon Invertebrate macrofauna. Methods To determine if surface area alone may generate the SAR, we conducted a small‐scale, ephemeral habitat island experiment in a subtidal soft‐bottom bay and in an intertidal soft‐bottom coastal salt marsh. Cellulose sponge habitat islands of varying surface areas, but with constant energy content and habitat diversity, were deployed in each location to isolate the effects of surface area on the SAR in the absence of species‐energy relationships and habitat diversity. Results Area alone, likely through passive sampling, generated significant SARs in both habitats, with the salt marsh producing the strongest relationship, likely due to differential physical structuring between habitats. Communities of low surface area sponges were generally nested within those of high surface area sponges, and dispersal limitation may have increased the importance of nestedness relative to species replacements in structuring communities between habitats. Main Conclusions That area alone, in the absence of covariates such as energy availability and habitat diversity may, significantly impact the species richness of experimental and ephemeral marine benthic habitat island communities. Our methodology may provide a new avenue for SAR research, allowing for the isolation and simultaneous testing of potential drivers through the physical manipulation of ephemeral habitats.

One mesh does not fit all: A dual compartment codend provides flexible selectivity opportunities to manage mixed fisheries - Junita D. Karlsen; Ludvig Ahm Krag; Bent Herrmann (Ocean & Coastal Management, 2024)

Seasonal and regional variability of model-based zooplankton biomass in the Salish Sea and evaluation against observations - Karyn D. Suchy; Elise Olson; Susan E. Allen; Moira Galbraith; BethElLee Herrmann; Julie E. Keister; R. Ian Perry; Akash R. Sastri; Kelly Young (Progress in Oceanography, 2023)

Evaluating the Safety of Intra-Articular Mitotherapy in the Equine Model: A Potential Novel Treatment for Osteoarthritis - Jennifer M. Cassano; Krzysztof Marycz; Marta Horna; Marcos Perez Nogues; Jessica M. Morgan; Daniel B. Herrmann; Larry D. Galuppo; Natalia Vapniarsky (Journal of Equine Veterinary Science, 2023)

Joint effects of climate, tree size, and year on annual tree growth derived from tree‐ring records of ten globally distributed forests - Kristina J. Anderson‐Teixeira; Valentine Herrmann; Christine R. Rollinson; Bianca Gonzalez; Erika B. Gonzalez‐Akre; Neil Pederson; M. Ross Alexander; Craig D. Allen; Raquel Alfaro‐Sánchez; Tala Awada; Jennifer L. Baltzer; Patrick J. Baker; et al. (Global Change Biology, 2022)
Tree rings provide an invaluable long‐term record for understanding how climate and other drivers shape tree growth and forest productivity. However, conventional tree‐ring analysis methods were not designed to simultaneously test effects of climate, tree size, and other drivers on individual growth. This has limited the potential to test ecologically relevant hypotheses on tree growth sensitivity to environmental drivers and their interactions with tree size. Here, we develop and apply a new method to simultaneously model nonlinear effects of primary climate drivers, reconstructed tree diameter at breast height (DBH), and calendar year in generalized least squares models that account for the temporal autocorrelation inherent to each individual tree's growth. We analyze data from 3811 trees representing 40 species at 10 globally distributed sites, showing that precipitation, temperature, DBH, and calendar year have additively, and often interactively, influenced annual growth over the past 120 years. Growth responses were predominantly positive to precipitation (usually over ≥3‐month seasonal windows) and negative to temperature (usually maximum temperature, over ≤3‐month seasonal windows), with concave‐down responses in 63% of relationships. Climate sensitivity commonly varied with DBH (45% of cases tested), with larger trees usually more sensitive. Trends in ring width at small DBH were linked to the light environment under which trees established, but basal area or biomass increments consistently reached maxima at intermediate DBH. Accounting for climate and DBH, growth rate declined over time for 92% of species in secondary or disturbed stands, whereas growth trends were mixed in older forests. These trends were largely attributable to stand dynamics as cohorts and stands age, which remain challenging to disentangle from global change drivers. By providing a parsimonious approach for characterizing multiple interacting drivers of tree growth, our method reveals a more complete picture of the factors influencing growth than has previously been possible.

A one year study of functionalised medium-chain carboxylic acids in atmospheric particles at a rural site in Germany revealing seasonal trends and possible sources - M. Teich; D. van Pinxteren; H. Herrmann (Journal of Atmospheric Chemistry, 2019)

N-Acetylcysteine Reverses Anxiety and Oxidative Damage Induced by Unpredictable Chronic Stress in Zebrafish - Ricieri Mocelin; Matheus Marcon; Simone D’ambros; Juliane Mattos; Adrieli Sachett; Anna M. Siebel; Ana P. Herrmann; Angelo Piato (Molecular Neurobiology, 2019)

Reduced spontaneous low frequency oscillations as measured with functional near-infrared spectroscopy in mild cognitive impairment - Julia B. M. Zeller; Andrea Katzorke; Laura D. Müller; Judith Breunig; Florian B. Haeussinger; Jürgen Deckert; Bodo Warrings; Martin Lauer; Thomas Polak; Martin J. Herrmann (Brain Imaging and Behavior, 2019)

Connectivity increases trophic subsidies in fragmented landscapes - Christine L. Hawn; John D. Herrmann; Sean R. Griffin; Nick M. Haddad (Ecology Letters, 2018)
Landscape corridors mitigate the negative effects of habitat fragmentation by increasing dispersal. Corridors also increase biodiversity in connected habitat fragments, suggestive of metacommunity dynamics. What is unknown in this case is the mechanisms through which metacommunity dynamics act. Working in a large‐scale fragmentation experiment, we tested the effect of corridors on the movement of prey species and subsequent effects on predator nutrition (which we call trophic subsidies). We enriched plants of central patches with 15 N, then measured δ 15 N in green lynx spiders, the most abundant insect predator, in patches that were either connected to or isolated from the enriched patch. We found that corridors increased prey movement, as they increased spider δ 15 N by 40% in connected patches. Corridors also improved spider body condition, increasing nitrogen relative to carbon. We suggest a novel mechanism, trophic subsidies, through which corridors may increase the stability or size of populations in connected landscapes.

ScalA-FS: expert-based ex-ante assessments of local requirements and success potential of upgrading strategies for improving food security in rural Tanzania - Götz Uckert; Frieder Graef; Anja Faße; Ludger Herrmann; Harry Hoffmann; Frederick C. Kahimba; Luitfred Kissoly; Hannes J. König; Christine Lambert; Henry Mahoo; Bashir Makoko; Leon Mrosso; et al. (Food Security, 2018)

Community resilience to tsunamis along the Southeastern Pacific: a multivariate approach incorporating physical, environmental, and social indicators - Paula Villagra; Marie Geraldine Herrmann; Carolina Quintana; Roger D. Sepúlveda (Natural Hazards, 2017)

Field studies measuring the aerosolization of endotoxin during the land application of Class B biosolids - R. F. Herrmann; R. J. Grosser; D. Farrar; R. B. Brobst (Aerobiologia, 2017)

Yield stability and adaptability of canola (Brassica napus L.) in multiple environment trials - Heping Zhang; Jens D. Berger; Chris Herrmann (Euphytica, 2017)

Vacant urban lot soils and their potential to support ecosystem services - Dustin L. Herrmann; William D. Shuster; Ahjond S. Garmestani (Plant and Soil, 2017)

Evaluation of nutria (Myocastor coypus) detection methods in Maryland, USA - Margaret A. Pepper; Valentine Herrmann; James E. Hines; James D. Nichols; Stephen R. Kendrot (Biological Invasions, 2017)

The role of digital data entry in participatory environmental monitoring - Jeremy R. Brammer; Nicolas D. Brunet; A. Cole Burton; Alain Cuerrier; Finn Danielsen; Kanwaljeet Dewan; Thora Martina Herrmann; Micha V. Jackson; Rod Kennett; Guillaume Larocque; Monica Mulrennan; Arun Kumar Pratihast; et al. (Conservation Biology, 2016)
Many argue that monitoring conducted exclusively by scientists is insufficient to address ongoing environmental challenges. One solution entails the use of mobile digital devices in participatory monitoring (PM) programs. But how digital data entry affects programs with varying levels of stakeholder participation, from nonscientists collecting field data to nonscientists administering every step of a monitoring program, remains unclear. We reviewed the successes, in terms of management interventions and sustainability, of 107 monitoring programs described in the literature (hereafter programs) and compared these with case studies from our PM experiences in Australia, Canada, Ethiopia, Ghana, Greenland, and Vietnam (hereafter cases). Our literature review showed that participatory programs were less likely to use digital devices, and 2 of our 3 more participatory cases were also slow to adopt digital data entry. Programs that were participatory and used digital devices were more likely to report management actions, which was consistent with cases in Ethiopia, Greenland, and Australia. Programs engaging volunteers were more frequently reported as ongoing, but those involving digital data entry were less often sustained when data collectors were volunteers. For the Vietnamese and Canadian cases, sustainability was undermined by a mismatch in stakeholder objectives. In the Ghanaian case, complex field protocols diminished monitoring sustainability. Innovative technologies attract interest, but the foundation of effective participatory adaptive monitoring depends more on collaboratively defined questions, objectives, conceptual models, and monitoring approaches. When this foundation is built through effective partnerships, digital data entry can enable the collection of more data of higher quality. Without this foundation, or when implemented ineffectively or unnecessarily, digital data entry can be an additional expense that distracts from core monitoring objectives and undermines project sustainability. The appropriate role of digital data entry in PM likely depends more on the context in which it is used and less on the technology itself.

Effects of zolpidem alone and in combination with nabilone on cannabis withdrawal and a laboratory model of relapse in cannabis users - Evan S. Herrmann; Ziva D. Cooper; Gillinder Bedi; Divya Ramesh; Stephanie C. Reed; Sandra D. Comer; Richard W. Foltin; Margaret Haney (Psychopharmacology, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Connectivity from a different perspective: comparing seed dispersal kernels in connected vs. unfragmented landscapes - John D. Herrmann; Tomás A. Carlo; Lars A. Brudvig; Ellen I. Damschen; Nick M. Haddad; Douglas J. Levey; John L. Orrock; Joshua J. Tewksbury (Ecology, 2016)
Habitat fragmentation can create significant impediments to dispersal. A technique to increase dispersal between otherwise isolated fragments is the use of corridors. Although previous studies have compared dispersal between connected fragments to dispersal between unconnected fragments, it remains unknown how dispersal between fragments connected by a corridor compares to dispersal in unfragmented landscapes. To assess the extent to which corridors can restore dispersal in fragmented landscapes to levels observed in unfragmented landscapes, we employed a stable‐isotope marking technique to track seeds within four unfragmented landscapes and eight experimental landscapes with fragments connected by corridors. We studied two wind‐ and two bird‐dispersed plant species, because previous community‐based research showed that dispersal mode explains how connectivity effects vary among species. We constructed dispersal kernels for these species in unfragmented landscapes and connected fragments by marking seeds in the center of each landscape with 15 N and then recovering marked seeds in seed traps at distances up to 200 m. For the two wind‐dispersed plants, seed dispersal kernels were similar in unfragmented landscapes and connected fragments. In contrast, dispersal kernels of bird‐dispersed seeds were both affected by fragmentation and differed in the direction of the impact: Morella cerifera experienced more and Rhus copallina experienced less long‐distance dispersal in unfragmented than in connected landscapes. These results show that corridors can facilitate dispersal probabilities comparable to those observed in unfragmented landscapes. Although dispersal mode may provide useful broad predictions, we acknowledge that similar species may respond uniquely due to factors such as seasonality and disperser behavior. Our results further indicate that prior work has likely underestimated dispersal distances of wind‐dispersed plants and that factors altering long‐distance dispersal may have a greater impact on the spread of species than previously thought.

Differential Accumulation of Mercury and Selenium in Brown Trout Tissues of a High-Gradient Urbanized Stream in Colorado, USA - S. J. Herrmann; D. R. Nimmo; J. S. Carsella; L. M. Herrmann-Hoesing; J. A. Turner; J. M. Gregorich; B. D. Vanden Heuvel; R. B. Nehring; H. P. Foutz (Archives of Environmental Contamination and Toxicology, 2016)

Association of Concurrent fNIRS and EEG Signatures in Response to Auditory and Visual Stimuli - Ling-Chia Chen; Pascale Sandmann; Jeremy D. Thorne; Christoph S. Herrmann; Stefan Debener (Brain Topography, 2015)

Chemical properties of HULIS from three different environments - T. B. Kristensen; L. Du; Q. T. Nguyen; J. K. Nøjgaard; C. Bender Koch; O. Faurskov Nielsen; A. G. Hallar; D. H. Lowenthal; B. Nekat; D. van Pinxteren; H. Herrmann; M. Glasius; et al. (Journal of Atmospheric Chemistry, 2015)

Confronting Uncertainty in Life Cycle Assessment Used for Decision Support - Ivan T. Herrmann; Michael Z. Hauschild; Michael D. Sohn; Thomas E. McKone (Journal of Industrial Ecology, 2014)
Summary The aim of this article is to help confront uncertainty in life cycle assessments (LCAs) used for decision support. LCAs offer a quantitative approach to assess environmental effects of products, technologies, and services and are conducted by an LCA practitioner or analyst (AN) to support the decision maker (DM) in making the best possible choice for the environment. At present, some DMs do not trust the LCA to be a reliable decision‐support tool—often because DMs consider the uncertainty of an LCA to be too large. The standard evaluation of uncertainty in LCAs is an ex‐post approach that can be described as a variance simulation based on individual data points used in an LCA. This article develops and proposes a taxonomy for LCAs based on extensive research in the LCA, management, and economic literature. This taxonomy can be used ex ante to support planning and communication between an AN and DM regarding which type of LCA study to employ for the decision context at hand. This taxonomy enables the derivation of an LCA classification matrix to clearly identify and communicate the type of a given LCA. By relating the LCA classification matrix to statistical principles, we can also rank the different types of LCA on an expected inherent uncertainty scale that can be used to confront and address potential uncertainty. However, this article does not attempt to offer a quantitative approach for assessing uncertainty in LCAs used for decision support.

Ground-level hyperspectral imagery for detecting weeds in wheat fields - I. Herrmann; U. Shapira; S. Kinast; A. Karnieli; D. J. Bonfil (Precision Agriculture, 2013)

Feedbacks underlie the resilience of salt marshes and rapid reversal of consumer‐driven die‐off - Andrew H. Altieri; Mark D. Bertness; Tyler C. Coverdale; Eric E. Axelman; Nicholas C. Herrmann; P. Lauren Szathmary (Ecology, 2013)
Understanding ecosystem resilience to human impacts is critical for conservation and restoration. The large‐scale die‐off of New England salt marshes was triggered by overfishing and resulted from decades of runaway crab grazing. In 2009, however, cordgrass began to recover, decreasing die‐off ∼40% by 2010. We used surveys and experiments to test whether plant–substrate feedbacks underlie marsh resilience. Initially, grazer‐generated die‐off swept through the cordgrass, creating exposed, stressful peat banks that inhibited plant growth. This desertification cycle broke when banks eroded and peat transitioned into mud with fewer herbivores, less grazing, and lower physical stress. Cordgrass reestablished in these areas through a feedback where it engineered a recovery zone by further ameliorating physical stresses and facilitating additional revegetation. Our results reveal that feedbacks can play a critical role in rapid, reversible ecosystem shifts associated with human impacts, and that the interplay of facilitative and consumer interactions should be incorporated into resilience theory.

Bioaccumulation of Selenium by the Bryophyte Hygrohypnum ochraceum in the Fountain Creek Watershed, Colorado - S. J. Herrmann; J. A. Turner; J. S. Carsella; D. W. Lehmpuhl; D. R. Nimmo (Environmental Management, 2012)

Development of polymorphic microsatellite loci for the rattlesnake species Crotalus atrox, C. cerastes, and C. scutulatus (Viperidae: Crotalinae) and cross-species amplification of microsatellite markers in Crotalus and Sistrurus species - Krystyn Pozarowski; D. Suzi Bryan; Rebekah Bosse; Eric Watson; Hans-Werner Herrmann (Conservation Genetics Resources, 2012)

H-D exchange on graphite–potassium intercalation compounds - Siegbert Rummel; Michael Herrmann; Manfred Wahren; Safar M. Yunusov; Margarita A. Ilatovskaya; Yuri B. Isaev; N. D. Lapkina; Yuri N. Novikov; Vladimir B. Shur (Isotopes in Environmental and Health Studies, 2012)

A trophic cascade triggers collapse of a salt‐marsh ecosystem with intensive recreational fishing - Andrew H. Altieri; Mark D. Bertness; Tyler C. Coverdale; Nicholas C. Herrmann; Christine Angelini (Ecology, 2012)
Overexploitation of predators has been linked to the collapse of a growing number of shallow‐water marine ecosystems. However, salt‐marsh ecosystems are often viewed and managed as systems controlled by physical processes, despite recent evidence for herbivore‐driven die‐off of marsh vegetation. Here we use field observations, experiments, and historical records at 14 sites to examine whether the recently reported die‐off of northwestern Atlantic salt marshes is associated with the cascading effects of predator dynamics and intensive recreational fishing activity. We found that the localized depletion of top predators at sites accessible to recreational anglers has triggered the proliferation of herbivorous crabs, which in turn results in runaway consumption of marsh vegetation. This suggests that overfishing may be a general mechanism underlying the consumer‐driven die‐off of salt marshes spreading throughout the western Atlantic. Our findings support the emerging realization that consumers play a dominant role in regulating marine plant communities and can lead to ecosystem collapse when their impacts are amplified by human activities, including recreational fishing.

Response of a Coupled Ocean–Atmosphere Model to Greenland Ice Melting - D. Stammer; N. Agarwal; P. Herrmann; A. Köhl; C. R. Mechoso (Surveys in Geophysics, 2011)

A study to discriminate local, urban and regional source contributions to the particulate matter concentrations in the city of Dresden, Germany - T. Gnauk; K. Müller; E. Brüggemann; W. Birmili; K. Weinhold; D. van Pinxteren; G. Löschau; G. Spindler; H. Herrmann (Journal of Atmospheric Chemistry, 2011)

Differential effects of habitat isolation and landscape composition on wasps, bees, and their enemies - Christof Schüepp; John D. Herrmann; Felix Herzog; Martin H. Schmidt-Entling (Oecologia, 2011)

Seasonal characteristics of tropical marine boundary layer air measured at the Cape Verde Atmospheric Observatory - L. J. Carpenter; Z. L. Fleming; K. A. Read; J. D. Lee; S. J. Moller; J. R. Hopkins; R. M. Purvis; A. C. Lewis; K. Müller; B. Heinold; H. Herrmann; K. Wadinga Fomba; et al. (Journal of Atmospheric Chemistry, 2010)

SWIR-based spectral indices for assessing nitrogen content in potato fields - I. Herrmann; A. Karnieli; D. J. Bonfil; Y. Cohen; V. Alchanatis (International Journal of Remote Sensing, 2010)

Resonance phenomena in the human auditory cortex: individual resonance frequencies of the cerebral cortex determine electrophysiological responses - T. Zaehle; D. Lenz; F. W. Ohl; C. S. Herrmann (Experimental Brain Research, 2010)

Thermodynamic properties of sea air - R. Feistel; D. G. Wright; H.-J. Kretzschmar; E. Hagen; S. Herrmann; R. Span (Ocean Science, 2010)
Very accurate thermodynamic potential functions are available for fluid water, ice, seawater and humid air covering wide ranges of temperature and pressure conditions. They permit the consistent computation of all equilibrium properties as, for example, required for coupled atmosphere-ocean models or the analysis of observational or experimental data. With the exception of humid air, these potential functions are already formulated as international standards released by the International Association for the Properties of Water and Steam (IAPWS), and have been adopted in 2009 for oceanography by IOC/UNESCO. In this paper, we derive a collection of formulas for important quantities expressed in terms of the thermodynamic potentials, valid for typical phase transitions and composite systems of humid air and water/ice/seawater. Particular attention is given to equilibria between seawater and humid air, referred to as "sea air" here. In a related initiative, these formulas will soon be implemented in a source-code library for easy practical use. The library is primarily aimed at oceanographic applications but will be relevant to air-sea interaction and meteorology as well. The formulas provided are valid for any consistent set of suitable thermodynamic potential functions. Here we adopt potential functions from previous publications in which they are constructed from theoretical laws and empirical data; they are briefly summarized in the appendix. The formulas make use of the full accuracy of these thermodynamic potentials, without additional approximations or empirical coefficients. They are expressed in the temperature scale ITS-90 and the 2008 Reference-Composition Salinity Scale.

Secondary structure and distribution of fusogenic LV-peptides in lipid membranes - J. Ollesch; B. C. Poschner; J. Nikolaus; M. W. Hofmann; A. Herrmann; K. Gerwert; D. Langosch (European Biophysics Journal, 2008)

Evolution of the Peak Hill high-sulfidation epithermal Au–Cu deposit, eastern Australia - Richard J. Squire; Walter Herrmann; Daniel Pape; D. Ian Chalmers (Mineralium Deposita, 2007)

Swiss Mattenklee landraces, a distinct and diverse genetic resource of red clover (Trifolium pratense L.) - R. Kölliker; D. Herrmann; B. Boller; F. Widmer (Theoretical and Applied Genetics, 2003)

Treatment of Severe Candida Infections in High-Risk Patients in Germany: Consensus Formed by a Panel of Interdisciplinary Investigators - Büchner T.; Fegeler W.; Bernhardt H.; Brockmeyer N.; Duswald K.-H.; Herrmann M.; Heuser D.; Jehn U.; Just-Nübling G.; Karthaus M.; Maschmeyer G.; Müller F.-M.; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Scenarios for Modeling Multiphase Tropospheric Chemistry - D. Poppe; B. Aumont; B. Ervens; H. Geiger; H. Herrmann; E.-P. Röth; W. Seidl; W. R. Stockwell; B. Vogel; S. Wagner; D. Weise (Journal of Atmospheric Chemistry, 2001)

Biosphere-atmosphere interactions of ammonia with grasslands: Experimental strategy and results from a new European initiative - M.A. Sutton; C. Milford; E. Nemitz; M.R. Theobald; P.W. Hill; D. Fowler; J.K. Schjoerring; M.E. Mattsson; K.H. Nielsen; S. Husted; J.W. Erisman; R. Otjes; et al. (Plant and Soil, 2001)

Analysis of single-nucleotide polymorphisms in the interleukin-4 receptor gene for association with inflammatory bowel disease - M. Olavesen; J. Hampe; M. M. Mirza; R. Saiz; C. M. Lewis; S. Bridger; D. Teare; D. F. Easton; T. Herrmann; G. Scott; J. Hirst; J. Sanderson; et al. (Immunogenetics, 2000)

Proving the Authenticity of Ancient DNA by Comparative Genomic Hybridization - S. Hummel; B. Herrmann; J. Rameckers; D. Müller; K. Sperling; H. Neitzel; H. Tönnies (The Science of Nature, 1999)

Caffeine and excitation–contraction coupling in skeletal muscle: a stimulating story - Annegret Herrmann-Frank; Hans-Christoph Lüttgau; D. George Stephenson (Journal of Muscle Research and Cell Motility, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Intraepidemic variants of influenza virus H3 hemagglutinin differing in the number of carbohydrate side chains - W. Seidel; F. Knkel; B. Geisler; W. Garten; B. Herrmann; L. Dhner; H. -D. Klenk (Archives of Virology, 1991)

Immunological characterization of the Marin County strain of astrovirus - J. E. Herrmann; W. D. Cubitt; R. W. Hudson; Dorothy M. Perron-Henry; L. S. Oshiro; N. R. Blacklow (Archives of Virology, 1990)

Differences of nucleoproteins of human and avian influenza a virus strains shown by polyacrylamide gel electrophoresis and by the peptide mapping technique - B. Geisler; W. Seidel; B. Herrmann; L. Dhner (Archives of Virology, 1986)